Cape Verde: Islands of Vulnerability or Resilience? A Transition from a MIRAB Model into a TOURAB One? - Eduardo Moraes Sarmento; Ana Lorga da Silva (Tourism and Hospitality, 2024)
Small island developing states (SIDSs) traditionally face a set of challenges like the weak and highly fragile economic configuration, environmental issues, and a traditional dependence on a few economic activities forcing them to open the economy to the exterior. Therefore, their development model, like in Cape Verde, depends on migration, remittances, dependence on aid, tourism, and state employment. The current research offers an insight into the nature of Cape Verde’s economy as a SIDS economy and the degree to which the country has been relying on tourism receipts, external remittances from migrations, aid programs, and government services. Understanding Cape Verde’s development model is important to clarify the challenges the country faces and its development needs to gather a long-term resilience and to understand if it is changing from a MIRAB (Migrations, Remittances, Aid, and Bureaucracy) model into another one.